Changes in hepatosomatic index and histoarchitecture of liver in common carp exposed to organophosphate insecticide sumithion - Hossain, Sabrina; Miah, Md Idris; Islam, Md Sadiqul; Shahjahan, Md (Asian Journal of Medical and Biological Research, 2016)
Sumithion is widely used in larval rearing aquaculture ponds to control aquatic insects. This experiment was carried out to evaluate the effect of sumithion on hepatosomatic index and liver morphology in common carp, Cyprinus carpio. Acute toxicity of sumithion (96 h LC50 value) was first determined and it was 8.05 ppm for common carp. The fish were exposed to two sub-lethal concentrations (0.85 and 1.7ppm) of sumithion for a period of 21 days. A control set was also run for the same time with the same number of fish without sumithion (0 ppm). There was a marked increase in the hepatosomatic index in both concentrations (0.85 and 1.70 ppm) compared to control (0 ppm). Several histological changes of liver, such as necrosis, patchy degeneration, degenerated hepatocytes, vaculation and blood spilling were observed after exposure to sumithion with dose and exposure time dependent manner. The present investigation revealed the toxic potentiality of sumithion on common carp which alters liver morphology that may lead metabolic changes in fish. Asian J. Med. Biol. Res. June 2016, 2(2): 164-170